Comparison of transient analysis of LBE-cooled fast reactor and ADS under loss of heat sink accident. (November 2015) - Wang, Gang; Gu, Zhixing; Wang, Zhen; Jin, Ming
Highlights: A natural circulation LBE-cooled research reactor is developed by Institute of Nuclear Energy Safety Technology. The safety advantages for 10 MWth fast and ADS reactors under loss of heat sink were compared. A neutronics and thermal-hydraulics coupled simulation code NTC was employed in this study. Abstract: A natural circulation LBE-cooled research reactor developed by Institute of Nuclear Energy Safety Technology (INEST) is proposed and designed to be 10 MWth . The reactor has two operation modes, which are LBE-cooled critical fast reactor mode and LBE-cooled accelerator-driven sub-critical system (ADS) reactor mode. In this paper, protected loss of heat sink (PLOHS) and unprotected loss of heat sink (ULOHS) transient accidents were simulated for both the critical and ADS reactors above by NTC-2D code, aiming at the investigation of the safety advantages for the two reactor modes under this typical transient condition (loss of heat sink, LOHS). The results showed that during PLOHS for both the two modes, all the key parameters (core power, fuel, cladding and coolant temperatures in the hottest channel) decreased to very small values after the reactor scrammed, which meant the reactors under the two modes were both safe. For ULOHS, the fuel, cladding and coolant temperatures of the fast reactor increased smaller than those of the sub-critical one, which means the fast reactor had a better safety advantage under LOHS transient.